2022
DOI: 10.3390/healthcare10091665
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Association between Fasting Plasma Glucose and Serum Selenium Levels in Adults from Southern Mexico

Abstract: Selenium (Se) is an essential trace element that by its antioxidant properties has been studied to elucidate its participation in the development of obesity and type 2 diabetes. We evaluated the association between cardiometabolic traits and serum Se levels in a sample of adults from southern Mexico. In 96 nondiabetic individuals, anthropometric data and clinical biochemistry measurements were analyzed. Serum total Se levels were measured with inductively coupled plasma mass spectrometry (ICP-MS). Serum Se lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Although Se has been recognized as an indispensable trace element, its effects remain a subject of debate. Several studies have suggested that Se possesses numerous health-enhancing effects, such as reducing fasting insulin ( 46 ), fasting plasma glucose ( 47 ) and serum CRP levels ( 48 ). In obese individuals, Se can decrease body fat mass and augment lean body and muscle mass ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although Se has been recognized as an indispensable trace element, its effects remain a subject of debate. Several studies have suggested that Se possesses numerous health-enhancing effects, such as reducing fasting insulin ( 46 ), fasting plasma glucose ( 47 ) and serum CRP levels ( 48 ). In obese individuals, Se can decrease body fat mass and augment lean body and muscle mass ( 49 ).…”
Section: Discussionmentioning
confidence: 99%